Developing Android Based Continuing Professional Development (CPD) Integrated Program for Primary School Teachers - Agusta, Okky Leo; Hamzah, Syukri (Jurnal Basicedu, 2022)
Teachers have a duty to continue to learn in developing their profession as educators. This study aimed to develop an Android-based application for the Integrated Teacher Continuous Professional Development Program (PT PKB Guru) to provide motivation and convenience for teachers in carrying out Continuous Professional Development activities: Self-Development, Scientific Publications, and Innovative Work. This study used the Research and Development method to develop a valid PT PKB Guru application and described the results of using the PT PKB Guru application. The results of this study indicated that the PT PKB Guru application was valid and could be used as an integrated application that guided teachers’ PKB activities. With the PT PKB Guru application, teachers were greatly helped in scheduled and coordinated training so that they can improve their scientific writing skills.